Bimodal structure formation and texture transition mechanism in laser remelted Mg–Al-based alloy - Lingxiao Ouyang; Xinyi Xie; Xiaohong Wang; Jingfeng Wang; Zihong Wang; Le Feng; Hongyun Li; Yunwei Gui; Fusheng Pan (Journal of Materials Research and Technology)
Texture inheritance, texture weakening, and a complete texture transition within different solidified molten pool (MP) have been achieved by manipulating various processing parameters of conduction mode in laser remelted magnesium-aluminum (Mg–Al)-based AZ31 alloy. At a low laser power (P = 100 W), restricted number of temperature gradient directions on moving solid/liquid (S/L) interfaces within small MP leads to strong texture inheritance. Tilting angles 20°–45° away from building direction (B.D.) in {0001} plane is a preferential growth direction of texture inheritance. In contrast, spontaneous texture weakening has occurred due to frequently varied temperature gradient directions within increasing MP size in higher P cases. Meanwhile, increasing scanning speed V has a significant effect on weakening the texture as well as refining grains in the solidified MP. Furthermore, fine grains formation with random orientations in MP bottom at both high P (400 W) and high V (20, 30, and 50 mm/s) leads to the occurrence of a bimodal structure, which is affected by solidification characteristics as well as thermal convection. For the case of the highest P and the highest V, a texture transition has occurred as tilting angles of 45°–90° away from B.D. in {0001} plane within MP, compared to 0°–45° texture of base material for the Mg–Al-based alloy in the study.